Dermatological Manifestations of Overweight and Obesity Among Adult Nepalese Population in a Tertiary Care Centre: A Case-Control Study - Sharma, Mukta; Agrawal, Sudha (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Introduction: Overweight and obesity are significant global public health concerns, with prevalence rising alarmingly in recent decades. Despite this, few studies have investigated the association between overweight/obesity and skin conditions. Objectives: This study aimed to assess the frequency of dermatological manifestations among overweight and obese adults attending a dermatology department and compare these findings with normal-weight, age- and sex-matched controls. Material and Methods: The study included 184 cases (BMI ≥ 25 kg/m²) and 184 controls (BMI 18.5–24.99 kg/m²) attending the dermatology outpatient department. Data were collected using a pre-designed pro forma, including clinical details and laboratory parameters. Skin conditions were categorized into overweight, Grade I, II, and III obesity. Univariate and multivariate logistic regressions were conducted to determine associations between BMI categories and skin diseases. Results: Among the cases, 60.3% were overweight, 21% were Grade I obese, and 8.7% were Grade II obese. Compared to controls, overweight and obese participants had a higher prevalence of skin conditions, including dermatophyte infections (29.3%), acanthosis nigricans (21.2%), and acrochordons (16.3%). Conclusion: Overweight and obesity are linked to various skin conditions, with most patients presenting at least one dermatological manifestation. These findings highlight the need for specialized dermatological care in this population.